Multiple-resonance phenomenon in neutrinoless double-electron capture - Eliseev, Sergey; Goncharov, M.; Blaum, Klaus; Block, M.; Droese, C.; Herfurth, F.; Minaya Ramirez, E.; Novikov, Yu. N.; Schweikhard, L.; Shabaev, V. M.; Tupitsyn, I. I.; Zuber, K.; et al. (Physical review. C, Nuclear physics, 2011)
A superposition of multiple resonance states in neutrinoless double-electron capture in 156Dy has been discovered. Penning-trap mass spectrometry has been used for atomic-mass-difference measurements and careful calculations of electron wave functions and double-hole binding energies have been performed to determine the resonance-enhancement factors. Transitions to four nuclear excited states in the daughter nuclide 156Gd have been identified as resonantly enhanced, including one with a full resonant enhancement, within the uncertainty of 100 eV. This phenomenon is unique in that it can be used to probe the mechanisms of neutrinoless processes.
Gesehen am 12.04.2022